Real-world gaseous and particle emissions of a Bi-fuel gasoline/CNG Euro 6 passenger car. (May 2020) - Dimaratos, A.; Toumasatos, Z.; Triantafyllopoulos, G.; Kontses, A.; Samaras, Z.
Highlights: Assessment of real driving emissions of a Euro 6 bivalent gasoline/CNG car. Complementary testing of a Euro 6 diesel passenger car, at the same routes. Two tests, one within RDE regulation, one beyond the limits with dynamic driving. CNG reduces CO and PN emissions, CO peaks in cold start and motorway with gasoline. NOx emissions penalty with CNG, local peaks in urban part. Abstract: The objective of the present study is the assessment of the environmental impact of a bivalent (bi-fuel) vehicle, running either on gasoline or compressed natural gas (CNG). To that aim, a Euro 6 passenger car was tested under various real-world driving conditions. In order to cover the full range of conventional powertrains currently in the market, the tests were also repeated on a Euro 6 diesel passenger car. Both cars were driven in two routes, the first complying with the regulation limits and the second going beyond them. Carbon monoxide (CO), nitrogen oxides (NOx ) and particle number (PN) emissions were recorded using a Portable Emissions Measurement System (PEMS). Apart from the aggregated emission levels, in g/km, the exact emission location along the route was also assessed. Natural gas proved beneficial for CO and PN emissions, the level of which always remained below the respective legislation limits. On the other hand, under the dynamic driving conditions with gasoline, the relevant limits were exceeded. Cold start, occurring at the beginning of the urban part, and motorway driving were identified as major contributors to total emissions, especially in gasoline mode. However, the application of natural gas was associated with a penalty in NOx emissions, which were significantly increased as compared to gasoline. Local peaks within the urban part were identified in CNG mode. In any case, the diesel vehicle was by far the highest NOx emitter.